Penyusunan Bahan Ajar Digital Akuntansi Keuangan Pada Sekolah SMK Permata Harapan - Anita Anita; Vivi Marlin (ConCEPt - Conference on Community Engagement Project, 2021)
This research is the result of compiling digital teaching materials financial accounting for Permata Harapan Vocational School. In order to prevent the spread of Covid-19, the government has established a study from home policy. Study policy from home is implemented while still involving educators and students through distance learning. The purpose of development is to produce digital teaching materials as a media in supporting the online teaching and learning process. The design of this practical work activity consists of observations and interviews, designing outputs, assisting the implementation of the outputs, and making reports. The target of this activity is to understand the obstacles that occur in financial accounting subjects experienced by schools. Study financial accounting subjects in accordance with the school curriculum, create and compile teaching materials on financial accounting. Teaching materials that have been compiled are teaching materials that are in accordance with the school's Core Competencies and Basic Competencies (KIKD).